2010
DOI: 10.1177/0146167210381650
|View full text |Cite
|
Sign up to set email alerts
|

Social Threats, Happiness, and the Dynamics of Meaning in Life Judgments

Abstract: Four studies examined social relatedness and positive affect (PA) as alternate sources of information for judgments of meaning in life (MIL). In Studies 1 through 3 (total N = 282), priming loneliness increased reliance on PA and decreased reliance on social functioning in MIL judgments. In Study 4 (N = 138), daily assessments of PA, relatedness needs satisfaction (RNS), and MIL were obtained every 5 days over 20 days. Multilevel modeling showed that on days when RNS was low, PA was strongly related to MIL. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 43 publications
7
67
1
1
Order By: Relevance
“…Experimental and correlational work by King et al (2006), for example, indicated that people who possess dispositional high positive affect or were induced with positive affect in turn reported greater perceived meaning in life. Follow-up research (Hicks et al 2010) further confirmed that everyday life positive affect is a key predictor of perceived meaning in life. We build on these earlier findings by recognizing the connection between perceptions of meaning and the experience of forms of positive affect, and in particular happiness.…”
Section: The Quest For Meaningmentioning
confidence: 85%
“…Experimental and correlational work by King et al (2006), for example, indicated that people who possess dispositional high positive affect or were induced with positive affect in turn reported greater perceived meaning in life. Follow-up research (Hicks et al 2010) further confirmed that everyday life positive affect is a key predictor of perceived meaning in life. We build on these earlier findings by recognizing the connection between perceptions of meaning and the experience of forms of positive affect, and in particular happiness.…”
Section: The Quest For Meaningmentioning
confidence: 85%
“…If we are correct that emotional clarity should help downregulate threats to meaning, then those who have a better understanding of their emotions should also be better able to cope with other threats to meaning, such as social exclusion (Hicks et al 2010). Additionally, naturalistic longitudinal designs could investigate whether emotional clarity is a resource for dealing with more extreme meaning threats, such as trauma or loss (Janoff-Bulman 1992).…”
Section: Discussionmentioning
confidence: 99%
“…To derive meaning from accomplishments (Ryff and Singer 1998), one may need to experience authentic pride with some degree of clarity (Tracy and Robins 2007). Additionally, close relationships provide meaning (Ryff and Singer 1998), but likely do so because they arouse feelings of love, belongingness, and acceptance (Hicks et al 2010). When clearly reflected upon, these emotions give people the impression that they are valued and that they play an important role in other peoples' lives (friend, confidant, guardian).…”
Section: Emotional Clarity Contributes To Meaningmentioning
confidence: 99%
See 1 more Smart Citation
“…Hicks & King, 2008Hicks, Trent, Davis, & King, 2012;King et al, 2006). The relationship between positive mood and meaning in life is especially strong when other sources of meaning in life are absent, lacking, or threatened (Hicks & King, 2008;Hicks, Schlegel, & King, 2010) and is amplified with age and limited time (Hicks et al, 2012). This very strong association is demonstrated, as well, in research showing that subliminal primes of words such as happy, jovial, and content lead to higher reports of meaning in life compared to a control condition, even though these words have no effect on explicit mood (King et al, 2006).…”
Section: Positive Affect and Meaningmentioning
confidence: 99%